Vilniaus universiteto bibliotekininkystės metodinė biblioteka - Striogienė, Aurelija (Information & Media, 1994)
This library was founded in 1987. The first books were received from the main University library and Lithuanian Technical library. In 1991 its stock contained 15,000 volumes. At that time the library had about 1,000 readers.The article describes library stock, acquisition, processing, circulation, main trends of automation. Students take active part in all those activities, especially dealing with library automation.